Tertiary EFL Female and Male Students’ Perception in Speaking Class: Gender-based Violence Issue - Dewi, Puspita; Yuliatin , Riyana Rizki; Sari , Dian Eka (SALEE: Study of Applied Linguistics and English Education, 2024)
Exploring how stories of gender-based violence boost students’ speaking. This article focuses on student’s experiences and captures phenomena of gender inequality, including sexual violence and domestic violence in the that may affect speaking . This study was implemented in the second semester for English literature students. The topic of gender violence was discussed in 14 meetings  to tell stories related to gender issues. This research results show that females and males have different perspectives the implementation of gender-based context in speaking class. The majority of females excited in learning English through social issues, particularly on gender violence matters. However, males prefer to discuss other topics relevant to males’ issues, and the learners do not really enjoy discussing the topics provided. All respondents agree that gender-based violence can boost students’ motivation in speaking and their critical thinking because the learners were encouraged to tell stories experience-based, and the pupils more aware violence. This contributes to a new insight for education field in distinguish two different perceptions for two sexes, particularly for educators, educational experts, and relevant stakeholders. Thereby, they can try to implement gender topics in teaching and learning process.